Microalgae as a Natural CO2 Sequester: A Study on Effect of Tobacco Smoke on Two Microalgae Biochemical Responses - Barati, Bahram; Fazeli Zafar, Fatemeh; Amani Babadi, Arman; Hao, Chen; Qian, Lili; Wang, Shuang; El-Fatah Abomohra, Abd (Frontiers in Energy Research, 2022)
Microalgae are known as the most efficient biological sequesters of carbon dioxide (CO2). Recently, they have been exploited to enhance air quality by decreasing CO2 levels and increasing oxygen (O2) concentrations. However, in public places, there are sources of toxic chemicals such as tobacco smoke that may affect the growth of microalgae. For the first time, the current study explores the influence of tobacco smoke on the cell growth, biodiesel characteristics, and biochemical composition of two strains of model microalgae. Chlamydomonas strains were treated with tobacco smoke in a sealed box for 7 days, wherein every 1 h, one cigarette was burnt. Upon exposure of microalgae to tobacco smoke, the specific growth rate (μmax) was unaffected in CHL-2220 and remained around 0.500 days−1, whereas in CHL-2221, it decreased notably from 0.445 days−1 to 0.376 days−1. In the CHL-2221, the lipid level considerably reduced from 15.55 %DW to 13.37 %DW upon exposure to tobacco smoke. In both strains, palmitic acid was the main constituent of saturated fatty acids (SFAs) that displayed significant (p < 0.05) decreases in response to tobacco smoke exposure. In CHL-2221, oleic acid (C18:1) presented a substantial increase from 7.64 to 17.09% in response to tobacco smoke. Moreover, exposure of CHL-2220 to tobacco smoke decreased the cetane number (CN) from 30.34 to 25.28, while in CHL-2221, it increased from 26.07 to 29.73 upon treatment. Both strains demonstrated low-quality biodiesel to be used as feedstock. Conversely, their fatty acid profile revealed their promising use as nutrient food.